The Influence of Leadership on Employee Discipline at PT. Bank Syariah Indonesia KCP Kampung Tax - Hastuti, Sri; Ria Armayani Hasibuan, Reni (CV. Lafadz Jaya, 2022)
This research was written using data collection techniques using questionnaires, as a technique of collecting data using a list of questions compiled by the author and submitted to the respondents, namely employees to answer the questions that have been provided. The results of these statistical calculations can lead to the conclusion that leadership has a strong influence on the work discipline of PT. Bank Syariah Indonesia KCP Kampung Tax contributed 46.77%. The relationship between the independent variable and the dependent variable forms the equation Y = 23.618+ 0.180X1+ 1.089X2. This equation shows that leadership is directly proportional to the work discipline of employees of PT. Bank Syariah Indonesia KCP Kampung Tax which means the better the leadership, the more self-disciplined employees of PT. Bank Syariah Indonesia KCP Kampung Tax will be increased.